Hubungan Sriwijaya dengan Dinasti Umayah terhadap Masuknya Agama Islam di Palembang pada Abad VIII Masehi - Wandiyo Wandiyo; Ida Suryani; Kabib Sholeh (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
The relationship between Srivijaya and foreign countries has long been established from China, India, Persia and also Arabia. The relationship between Srivijaya and Arabic precisely with the Umayyad dynasty has been well established so that the relationship has a positive impact on the process of entering Islam in Palembang in the 8th century AD. The purpose of this study was to analyze the relationship between Srivijaya and the Umayyad dynasty in various aspects and to analyze the impact of the relationship on the process of entering Islam in Palembang. The method used in this study is the historical method carried out with several steps starting from heuristics, verification, interpretation and historiography. Data collection techniques use heuristics and verification. Data analysis techniques use historical interpretations with the help of other fields of scientific approach. The relationship between Srivijaya and the Umayyad dynasty had occurred in the 8th century AD, where the relations between the two rulers continued very well so that the sending of letters from Srivijaya to the Umayyans, during the reign of Umar bin Abdul Aziz, was up to twice recorded in the shipment. In this connection there is certainly a mutually beneficial cooperative relationship in the political and economic fields. In the economic aspects of Muslim traders who came to the center of Srivijaya in Palembang indirectly had a positive effect on the spread of Islam, especially in Palembang. Muslim traders came and went to Palembang to trade with Srivijaya.